The Woman In White - Collins Wilkie (Hong Kong Oxford University Press, 1993)
This popular series of readers has now been completely revised and updated, using a new syllabus and new word structure lists. Words that are above a certain level but essential to the story are explained within the text, illustrated and then reused for maximum reinforcement.
Novel
Keywords: English Literature